Factors Associated with Exclusive Breastfeeding at the Bulili Health Center, South Bureaubuli Village, Palu City - Nurul, Rasyika; Mukhlishah, Nurul; Radhiah, Sitti; Patui, Nurhaya S.; Yani, Ahmad; Krisnasari, Sendhy (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Exclusive breastfeeding is the best nutrient for babies. The impacts of not receiving exclusive breastfeeding are infection, high risk of infectious diseases such as diarrhea and pneumonia, low immune system, and decreased brain development. breastfeeding reduces baby and toddler morbidity and mortality. Human milk glycans, which contain oligosaccharides in both their free and conjugated forms, are demonstrated in studies to be a component of a natural immune process that explains how human milk protects breastfed children from diarrheal illness. This study aims to analyze factors associated with exclusive breastfeeding in the work area of Bulili Public Health Center South Birobuli Subdistrict Palu. This quantitative research was conducted through a cross-sectional approach. This study involved 90 mothers with babies aged 7-12 months, which was carried out from March 2023. The sample was selected using simple random sampling based on inclusion criteria. Direct interviews were used to collect primary data, and secondary data were obtained from Indonesia's health profile, data from the Palu City Health Office 2021, and data on exclusive breastfeeding. The data were processed using the chi-square statistical test with a significance degree of α = 0.05. The results of the study were knowledge (p=0.018), attitude (p=0.001), interest in formula milk promotion (p=0.018), and family support (p=0,002). In Conclusion, there is a significant association between knowledge, attitude, interest in formula milk promotion, and family support with exclusive breastfeeding practice. It is suggested for mothers to increase knowledge, attitude, and family support by gaining information and using social media appropriately.